2019
DOI: 10.1097/pas.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry for PRAME in the Distinction of Nodal Nevi From Metastatic Melanoma

Abstract: The distinction of metastatic melanoma from melanocytic nevi in lymph nodes can on occasion be difficult. As diffuse immunohistochemical (IHC) PRAME (PReferentially expressed Antigen in MElanoma) expression is detected in the majority of primary and metastatic melanomas, but rarely in nevi, we reasoned that PRAME could be a useful adjunct marker for the diagnosis of melanocytes in lymph nodes. In this study, we examined 45 nodal melanocytic deposits comprising 30 nodal nevi and 15 melanoma metastases. The latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 24 publications
10
110
0
2
Order By: Relevance
“…More recently, PRAME has been described to be a helpful marker in distinguishing nodal nevi from metastatic melanoma, but it needs to be validated in larger series. 29 Finally, this study also showed that expert pathology review…”
Section: Histopathological Evaluation Of Snsupporting
confidence: 58%
“…More recently, PRAME has been described to be a helpful marker in distinguishing nodal nevi from metastatic melanoma, but it needs to be validated in larger series. 29 Finally, this study also showed that expert pathology review…”
Section: Histopathological Evaluation Of Snsupporting
confidence: 58%
“…We note that the threshold for defining diffuse staining in our cohort (60%) differs from the cutoff of 75% established by Lezcano et al 14,15,19 Six of our 24 non‐spitzoid melanomas (25%), none of which were desmoplastic, would be considered non‐diffuse with the higher cutoff, and no Spitz nevi would have shown diffuse expression. Given that rare examples of diffuse PRAME staining in non‐malignant spitzoid neoplasms reinforce the need to perform additional studies for definitive classification in this diagnostic category, we selected a threshold that prioritized the ability of PRAME to discriminate between benign and malignant non‐spitzoid neoplasms.…”
Section: Discussionmentioning
confidence: 60%
“…A summary of PRAME results by type of lesion is provided in We note that the threshold for defining diffuse staining in our cohort (60%) differs from the cutoff of 75% established by Lezcano et al 14,15,19 Six of our 24 non-spitzoid melanomas (25%), none of which were desmoplastic, would be considered non-diffuse with the higher In summary, this study expands on the diagnostic utility of PRAME by demonstrating its lack of diffuse expression in atypical but benign melanocytic proliferations, facilitating their distinction from melanoma. This study also reinforces that PRAME expression in spitzoid neoplasms should be interpreted in the context of histopathologic features, and correlation with cytogenetic and/or molecular studies may be required for diagnostic classification.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations